2022
DOI: 10.3389/fnagi.2022.1037650
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between sleep duration and cognitive impairment in Chinese elderly

Abstract: BackgroundAge-associated cognitive decline has become a major threat to both personal welfare and public health and can further develop into Dementia/Alzheimer’s disease. Sleep is significantly correlated with cognitive function, but both cognitive impairment and sleep problems increase with normal aging. This study explored how sleep duration affects cognitive performance among older adults in China.MethodsUsing data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2014 and 2018, cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Specifically, games like Mahjong, are considered to improve memory accuracy and reaction ability ( 29 , 67 ). Our research findings align with these previous studies ( 29 , 32–35 ). Moving to the data from 2011, older people who played Mahjong not only exhibited higher scores in attention and calculation but also demonstrated higher scores in language, understanding, and self-coordination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, games like Mahjong, are considered to improve memory accuracy and reaction ability ( 29 , 67 ). Our research findings align with these previous studies ( 29 , 32–35 ). Moving to the data from 2011, older people who played Mahjong not only exhibited higher scores in attention and calculation but also demonstrated higher scores in language, understanding, and self-coordination.…”
Section: Discussionsupporting
confidence: 93%
“…The Mini-Mental State Examination (MMSE), also known as the Mini-Mental State Exam or the Simple Mental State Examination, was developed by Folstein et al in 1975 ( 31 ). The questionnaire encompasses an evaluation of five dimensions of cognitive function: general ability, reaction ability, attention and calculation abilities, recall capability, and self-coordination ability ( 32 ). It stands as one of the most influential standardized tools for assessing intellectual status.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this study confirmed that sleep quality was correlated with sociodemographic data such as sex, marital status, and education level. According to another recent nationwide cross-sectional study conducted in China, excessive sleep duration rather adversely affects the cognitive function of the elderly population ( 28 ). In addition, a US study of 25,962 people with an average age of 48.1 years concluded that sleep duration was independently associated with a high incidence of depression ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The validity and reliability of this questionnaire have been validated in previous studies ( 17 , 18 ). Cognitive dysfunction in this study was defined using the criteria of Zhang et al ( 17 ) and Chen et al ( 19 ), whereby a MMSE score < 18 indicated cognitive dysfunction. Additional information regarding the MMSE scores of the participants is shown in Table SII .…”
Section: Methodsmentioning
confidence: 99%